Macroscopic changes in puppies with experimental coronaviral enteritis - Радзиховський, М. Л. (Scientific Progress & Innovations, 2018)
On the basis of our analysis of literary sources, the results of monitoring and our own research, it was found out that viral enteritis occupies a leading place in the infectious pathology of dogs and causes significant damage to animal owners. Taking into account the relevance of this issue, the result of our research is specification, supplement and generalization of the data on the pathomorphology of various organs of dogs for coronaviral enteritis, which will give an opportunity to more precisely determine the effect of the pathogen on the animal's body. The purpose of this work was to study and characterize the pathomorphological changes in the large intestine in experimental contamination of dogs with coronavirus enteritis. The work was carried out at the Faculty of Veterinary Medicine of Zhytomyr National Agroecological University (ZNAEU). Thanatopsy of the animals was carried out in the special laboratory of the Department of Anatomy and Histology. The article presents the results of the study of macroscopic changes in dogs in experimental reproduction of coronaviral enteritis. According to the results of the pathological anatomical section of the corpses of the puppies, microscopic changes in the internal organs are observed, namely, serous lymphadenitis, thymus and pancreas, edema and hyperemia, the kidneys are irregularly brown-colored, liver, heart as well as vessels of the brain and spinal cord are enlarged. Thus, our complex of pathoanatomical changes in puppies in the experimental reproduction of the disease has been identified by us as a characteristic criterion for the pathomorphological diagnosis of coronaviral enteritis in dogs. In the future, in order to fully cover the pathomorphological picture of the disease, it is advisable to carry out histological examination of the organs and tissues in the dog-infected Coronaviridae.